The Effect of Leg Explosive Strength Training on Lay-Up Shoot Ability in Basketball Games Students at SMA Negeri 3 Pinrang - Hariani, Harian; Sahabuddin, Sahabuddin; Sudidharma, Sudiadharma (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This research aims to determine: (1) The effect of skipping training on the ability to lay-up the shoot in basketball games among students at SMA Negeri 3 Pinrang; (2) The effect of bench jumping practice on lay-up shoot ability in basketball games among students at SMA Negeri 3 Pinrang and (3) The difference in the influence of skipping practice and bench jumping practice on lay-up shoot ability in basketball games for students at SMA Negeri 3 Pinrang. The population of this study were all students of SMA Negeri 3 Pinrang with a research sample of 20 students selected as a total population and a group division system using ordinal maching. The data analysis techniques used are descriptive, data normality tests, homogeneity tests and t-tests using the SPSS program. The research results show that; (1) There is an influence of skipping training on lay-up shooting ability in basketball games among Pinrang 3 Public High School students. The ability to lay-up the shoot in the game of basketball among SMA Negeri 3 Pinrang students is proven by an increase from an average score of 3.0000 to 5.9000; (2) There is an effect of upright bench training on the ability to lay-up the shoot in basketball games among students at SMA Negeri 3 Pinrang. The ability to lay-up the shoot in the game of basketball among students at SMA Negeri 3 Pinrang is proven by an increase from an average score of 3.0000 to 7.900 (3) There is a difference in the influence between skipping practice and bench jumping practice on the ability to lay-up shoot in the game of basketball in student at SMA Negeri 3 Pinrang. The ability to lay-up and shoot in the game of basketball for SMA Negeri 3 Pinrang students is 5.9000 > 7.9000. The conclusion is that bench jumping training has a greater influence than skipping training on lay-up shooting ability in basketball games among students at SMA Negeri 3 Pinrang.